Panama: An Open-Source Educational App for Ion Channel Biophysics Simulation - Rajbanshi, Binita; Guruacharya, Anuj (Frontiers in Neuroinformatics, 2022)
This article describes an open-source educational software, called Panama, developed using R, that simulates the biophysics of voltage-gated ion channels. It is made publicly available as an R package called Panama and as a web app at http://www.neuronsimulator.com. A need for such a tool was observed after surveying available software packages. Available packages are either not robust enough to simulate multiple ion channels, too complicated, usable only as desktop software, not optimized for mobile devices, not interactive, lack intuitive graphical controls, or not appropriate for educational purposes. This app simulates the physiology of voltage-gated sodium, potassium, and chlorine channels; A channel; M channel; AHP channel; calcium-activated potassium channel; transient-calcium channel; and leak-calcium channel, under current-clamp or voltage-clamp conditions. As the input values on the app are changed, the output can be instantaneously visualized on the web browser and downloaded as a data table to be further analyzed in a spreadsheet program. This app is a first-of-its-kind, mobile-friendly, and touchscreen-friendly online tool that can be used as an installable R package. It has intuitive touch-optimized controls, instantaneous graphical output, and yet is pedagogically robust for educational purposes.